A Pareto-Optimal Carbon Allowance Policy – Balancing Emission Reduction and Commuter Benefits in Urban Transportation Systems - YANG, Yaqi; ZHANG, Xiaoning; MARSDEN, Greg (Promet - Traffic&Transportation, 2025)
This paper explores the impact of the personal carbon allowance (PCA) policy on a bi-modal transportation system, examining travel mode shifts, congestion patterns and policy effectiveness. The optimal carbon allowance quantity and the policy’s social acceptability are assessed through numerical simulations and Pareto optimisation. Results indicate that, in this parametric simulation, a strict allocation of 8,650 units achieves a 64% emission reduction while meeting Pareto efficiency, whereas a higher allowance of 14,300 units prioritises public acceptance with a 41% emissions reduction. However, the effectiveness of the PCA policy is influenced by factors such as road capacity stability and the level of public transportation development. First, low or unstable road capacity diminishes behavioural shifts and carbon emission reductions. However, when accidents are promptly addressed, the policy’s effectiveness is less impacted. Second, if public transit capacity is insufficient and passengers experience overcrowding, reducing car commuters without undermining passenger benefits proves challenging. The study quantifies the trade-offs between emission reduction goals and societal welfare, identifies infrastructure limitations and demonstrates the policy’s adaptability through dynamic adjustments. Although assuming homogeneous traveller behaviour and static demand, this work establishes a framework for implementing behaviourally-informed carbon allowances policy in real-world transport systems.